1989
DOI: 10.1051/rnd:19890110
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutrition in ewes : effects of low to high iodine intake on iodine content of biological fluids in pregnant and lactating ewes

Abstract: Summary ― In a first experiment, 2 groups of 46 and 47 multiparous ewes received diets which provided an iodine intake of 0.36 and 0.26 mg/kg dry matter (group C) and, 2.01 and 1.94 mg/kg (group D), respectively, for pregnancy and lactation. In a second experiment, 3 groups of 10 nulliparous ewes received diets which provided an I intake of 0.13 and 0.12 mg/kg dry matter (group A), 0.22 and 0.20 mg/kg dry matter (group B), and 10.77 and 8.88 mg/kg dry matter (group E), respectively, for pregnancy and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(23 reference statements)
1
8
1
Order By: Relevance
“…On farm A this difference was found in both experimental and control animals (Figure 1), whereas on farm B a significant colostrum/milk difference was determined only in the experimental sows (Figure 2). This result corresponds with the measurements by Aumont et al (1989), who found 1.5 to 6.7-fold higher amounts of iodine in colostrum compared to its amount in milk depending on the level of iodine supplementation to pregnant ewes.…”
Section: Resultssupporting
confidence: 91%
“…On farm A this difference was found in both experimental and control animals (Figure 1), whereas on farm B a significant colostrum/milk difference was determined only in the experimental sows (Figure 2). This result corresponds with the measurements by Aumont et al (1989), who found 1.5 to 6.7-fold higher amounts of iodine in colostrum compared to its amount in milk depending on the level of iodine supplementation to pregnant ewes.…”
Section: Resultssupporting
confidence: 91%
“…This could explain why, despite a lower I content in the thyroid gland, the thyroxine secretion rate of the lambs was not impaired, whereas it was impaired in the dams during lactation (Aumont et al, 1989). In any case, 0.12 mg of I/kg DM can be assumed to be the lowest limit for I intake before a deficiency occurs in lactating ewes and in their fetuses and lambs at birth.…”
Section: Analysesmentioning
confidence: 97%
“…The right thyroid lobes were homogenized in 5 ml of sodium chloride solution (0.154 mol/I) with a Potter Elvehjem homogenizer. The total I content of the thyroid lobes was determined in 0.5 ml of homogenized tissue (Aumont and Tressol, 1986 (Aumont et al, 1989). Analysis of variance-covariance (Seebeck, 1973) (Siegel, 1956) (Table IV).…”
Section: Analysesmentioning
confidence: 99%
See 2 more Smart Citations